Anthropometric characteristics of rhythmic gymnasts - Jelena Lukić (University of Novi Sad, Faculty of Sport and Physical Education, 2020)
In esthetic sports, such as rhythmic gymnastics, body size and body composition can directly affect performance and outcome. The aim of this study was to identify anthropometric characteristics and to notice their impact on the prediction of higher performance in rhythmic gymnastics. For the needs of this review, scientific literature was analyzed from prestigious scientific journals. This systematic review included available data from the following databases: Google Scholar, Springer, PubMed, Europe PMC and research databases. Studies with the following criteria were included: anthropometric characteristics, profile or status and somatic constitution, body composition, somatotypes and morphological models, factors influencing performance and the level of the performance (reliability), and being published in English and Serbian language. Out of total 52 studies, reviewed 9 studies met the inclusion criteria. Based on the findings of the present study it could be concluded that anthropometric characteristics are an important item on the basis of which talent identification, sports selection and programming of training and nutrition plan is performed.